2011
DOI: 10.1590/s1807-76922011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Using social networks theory as a complementary perspective to the study of organizational change

Abstract: This paper contributes to the literature on organizational change by examining organizations as social entities embedded in inter-organizational networks. In contrast with extant research that focuses on macro environmental and internal factors to explain organizational change, we put forth the social network surrounding the firm as a major driver of any change process. Specifically, we examine organizational change as driven by the organizations' positions and relations in an interorganizational network, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 80 publications
0
11
0
1
Order By: Relevance
“…An understanding of organizational change is necessary to understanding organizations themselves and can be investigated from various perspectives (Ferreira and Armagan, 2011). Within the literature surrounding organizing and organization there are multiple typologies (for example: first, second and third order change (Bartunek and Michael, 1987); Life Cycle Theory, Evolution, Dialectic and Teleological ( Van de Ven and Poole, 1995) and models of change presented (Sturdy and Grey, Beneath and beyond organizational change (Sturdy and Grey, Beneath and beyond organizational change management: exploring alternatives, 2003;Schein, 1995).…”
Section: Planned Changementioning
confidence: 99%
See 2 more Smart Citations
“…An understanding of organizational change is necessary to understanding organizations themselves and can be investigated from various perspectives (Ferreira and Armagan, 2011). Within the literature surrounding organizing and organization there are multiple typologies (for example: first, second and third order change (Bartunek and Michael, 1987); Life Cycle Theory, Evolution, Dialectic and Teleological ( Van de Ven and Poole, 1995) and models of change presented (Sturdy and Grey, Beneath and beyond organizational change (Sturdy and Grey, Beneath and beyond organizational change management: exploring alternatives, 2003;Schein, 1995).…”
Section: Planned Changementioning
confidence: 99%
“…This is in relation to a trigger which stimulates the organization to start the change process (Ferreira and Armagan, 2011) by creating a sense of concern and developing a commitment to change (Phillips, 1983). Huber et al (1993) identify 5 triggers of change; structure, strategy, characteristics of top management, macro-economic and performance while others have examined the role of innovation in triggering change (Ferreira and Armagan, 2011;Greve and Taylor, 2000). Schein (1995) argues that for this unfreezing to occur, there must be form of dissatisfaction or disconfirmation of the existing process or data and that the people who make up the organization must feel 'survival anxiety or guilt' to accept the disconfirming information.…”
Section: Planned Changementioning
confidence: 99%
See 1 more Smart Citation
“…Bowler et al (2010) defined that a team was consisted of two or more members who mutually coordinated with each other to complete the common task. Ferreira and Armagan (2011) indicated that a team should not simply stress on the achievement of overall objectives, but should emphasize the dependence and mu-tual commitment among members. Hartnell et al (2011) regarded a team being composed of few people with complementary skills; such people agreed with a common objective and the process for which they would undertake the responsibilities.…”
Section: Leadershipmentioning
confidence: 99%
“…(Ferreira & Armagan, 2011); a investigação do papel das lideranças em mudanças planejadas (Kotter, 1995;Oreg & Berson, 2011;Seo et al, 2012); a interação entre componentes da estrutura e tipo de mudança (Voet, 2014); abordagens processuais da mudança (Tsoukas & Chia, 2002;Van de Ven & Poole, 2005); e o estudo das percepções e reações dos indivíduos (Hernandez & Caldas, 2001;Neiva e Paz, 2007;Vakola, Armenakis & Oreg, 2013) e equipes (Guiette & Vandenbempt, 2013).…”
Section: Weick E Quinn (1999)unclassified